Knowledge, Family and Social Support, Self Efficacy and Self-Care Behaviour in Pulmonary Tuberculosis Patients - Sukartini, Tintin; Hidayati, Laily; Khoirunisa, Navisa (Jurnal Keperawatan Soedirman, 2019)
Tuberculosis is a disease that requires lengthy treatment. Knowledge of tuberculosis as well as family and social support are considered as important components of efficacy decisions. This study was conducted to analyse the relationship between knowledge, family and social support and self-efficacy and self-care behaviour in patients with pulmonary tuberculosis. The research used a cross sectional design. The population were 77 people and 65 respondents were obtained using a purposive sampling technique. Instruments used were knowledge, family support, social support, self-efficacy and self-care behaviour questionnaires. The data analysis method used was the Spearman rho test with a significance value of ??0.05. There were significant correlations between knowledge (p=0.003) and family support (p=0.000) and self-efficacy. There was no correlation between social support (p=0.106) and self-efficacy. There was a correlation between knowledge (p=0.048), family support (p=0.036) and social support (p=0.022) and self-care behaviour. There was a relationship between knowledge and family support and self-efficacy, whereas social support had no relationship with self-efficacy. There was a relationship between knowledge, family support and social support and self-care behaviour. Future researchers are expected to be able to design quasi experimental research to determine cultural differences (habits) in patients with pulmonary tuberculosis